PROPERTIES OF INSTUITIONISTIC FUZZY SP-BOUNDARY - Karthika, A. (Journal of Global Research in Mathematical Archives(JGRMA), 2013)
In this paper we present a new concept of Intuitionistic fuzzy Â SP-boundary via the arbitrary complement function namely: [0, 1]Â [0, 1] introduced in recent years. The fuzzy Â Â -closure operator is used as a tool to derive some of their characterizations. Keywords and phrases: Intuitionistic fuzzy set, Intuitionistic fuzzy topological spaces, Fuzzy boundary, Fuzzy semi-pre boundary. Mathematics Subject Classification: 54A40